Safety at work law and negligent behaviour in relation to public vehicle accidents in Cameroon - Encho, Quinta Ewoh; Ab. Rahman, Rozanah; Mohd Tamrin, Shamsul Bahri; How, Vivien (Journal of Human Factors and Ergonomics Society Malaysia, 2019)
It is not unlikely in Cameroon to be involved in road accidents.The debate as to who is responsible has been a bone of contention among travellers for years. Some have put the blame on the government for inadequate laws and road unworthiness. Others blamed the drivers for being ‘cash crazy’ and reckless while others have blamed the companies for hiring drivers that are not qualified and not putting safety policies in place. In all these cases, the degree of accidents that had taken place on these roads is alarming and someone therefore has to shoulder the responsibility for there to be a change. This article reviews the concept of the law of negligence citing cases of negligent behaviours from all partiesinvolved. The aim of this article is to create awareness on the ongoing cases of accidents, both reported and unreported for government intervention and to raise public awareness.